2018
DOI: 10.34127/jrlab.v7i1.221
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Quality of Work Life (Qwl) Dan Organizational Climate Terhadap Kepuasan Kerja Yang Berimplikasi Pada Organizational Citizenship Behaviour (Ocb) Karyawan Di Politeknik Lp3i Jakarta

Abstract: <p>ABSTRACT</p><p>This research has a purpose to find out: the effect of Quality of Work Life (QWL) on Job Satisfaction in LP3I Polytechnic Jakarta; the effect of Organizational Climate on Job Satisfaction in LP3I Polytechnic Jakarta; the effect of Quality of Work Life (QWL) on Organizational Citizenship Behavior (OCB) at the Polytechnic LP3I Jakarta; the effect of Organizational Climate on Organizational Citizenship Behavior (OCB) at the Polytechnic LP3I Jakarta; the effect Job Satisfaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
1
1
0
Order By: Relevance
“…499-506 504 Journal homepage: https://jurnal.iicet.org/index.php/jppi The proceeds of the Sobel test are presented in Table 5 reveal that the p-value is 0.022 < 0.05, thus Hypothesis 6 is accepted or it can be interpreted that Quality of Work Life (QWL) affects Organizational Citizenship Behavior (OCB) through Job Satisfaction as a mediating variable. This corresponds with the report of Ardila, et al (2018) who investigated the effect of Quality of Work Life (Qwl) and Organizational Climate on Job Satisfaction which had implications for Organizational Citizenship Behavior OCB). Therefore, the results of this study indicate that the impact is positive and significant: QWL on Job Satisfaction.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…499-506 504 Journal homepage: https://jurnal.iicet.org/index.php/jppi The proceeds of the Sobel test are presented in Table 5 reveal that the p-value is 0.022 < 0.05, thus Hypothesis 6 is accepted or it can be interpreted that Quality of Work Life (QWL) affects Organizational Citizenship Behavior (OCB) through Job Satisfaction as a mediating variable. This corresponds with the report of Ardila, et al (2018) who investigated the effect of Quality of Work Life (Qwl) and Organizational Climate on Job Satisfaction which had implications for Organizational Citizenship Behavior OCB). Therefore, the results of this study indicate that the impact is positive and significant: QWL on Job Satisfaction.…”
Section: Resultssupporting
confidence: 82%
“…Narzary and Palo (2019) observed the relationship of spirituality and job satisfaction to OCB, the outcomes showed that job satisfaction had a significant and positive effect on OCB. Ardila, et al (2018) observed the influence of QWL and Organizational Climate on Job Satisfaction which had implications for OCB, the results of this study pointed out that the impact was positive and significant for QWL on Job Satisfaction and OCB.…”
Section: H3: Work Motivationis Expected To Have a Direct Effect Onorg...mentioning
confidence: 52%